Pyrosequencing detects human and animal pathogenic taxa in the grapevine endosphere - Yousaf, Sohail; Bulgari, Daniela; Bergna, Alessandro; Pancher, Michael; Quaglino, Fabio; Casati, Paola; Campisano, Andrea (Frontiers in Microbiology, 2014)
Generally, plants are not considered as hosts for human and animal pathogens (HAP). The recent produce-associated outbreaks of food-borne diseases have drawn attention towards significant deficiencies in our understanding of the ecology of HAP, and their potential for interkingdom transfer. To examine the association of microorganisms classified as HAP with plants, we surveyed the presence and distribution of HAP bacterial taxa (henceforth HAPT, for brevity’s sake) in the endosphere of grapevine (Vitis vinifera L.) both in the plant stems and leaves. An enrichment protocol was used on leaves to detect taxa with very low abundance in undisturbed tissues. We used pyrosequencing and phylogenetic analyses of the 16S rDNA gene. We identified several HAPT, and focused on four genera (Propionibacterium, Staphylococcus, Clostridium, and Burkholderia). The majority of the bacterial sequences in the genus Propionibacterium, from grapevine leaf and stem, were identified as P. acnes. Clostridia were detected in leaves and stems, but their number was much higher in leaves after enrichment. HAPT were indentified both in leaves and wood of grapevines. This depicts the ability of these taxa to be internalized within plant tissues and maintain their population levels in a variety of environments. Our analysis highlighted the presence of HAPT in the grapevine endosphere and unexpected occurrence of these bacterial taxa in this atypical environment.